Motif Batik Tradisional Khas Pangkalan Brandan sebagai Simbol Peristiwa Bumi Hangus Pangkalan Brandan - Maysaroh, Maysaroh; Lestari, Ayu; Siregar, Yusra Dewi (Local History & Heritage, 2024)
This article explores the history of the distinctive batik motifs from Kampong Batik Brandan, which hold unique characteristics and serve as a representation of the "Bumi Hangus" event, commemorated through the art of batik. Given that batik is a high-value art form, this led to the establishment of a venue dedicated to preserving cultural history and art in Pangkalan Brandan, known as Kampong Batik Brandan. This study employs a qualitative research method, utilizing interviews with sources and additional information collected through literature review. The findings reveal that the creation of Malay batik, particularly Brandan batik, has become iconic due to the historical narrative embedded in its motifs, symbolizing the heroic "Bumi Hangus" event known in the area. This community’s commitment to preserving history and culture inspired the establishment of Kampong Batik Brandan as a space for sustaining cultural and historical creativity.